English Teachers' Perception of the Use and Challenge of YouTube Videos in Vocabulary Learning at Junior High Schools in Penajam Paser Utara - Awalia Fitratul Jannah Oktavia; Weningtyas Parama Iswari; Kurniawan Suryatama (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2026)
This study examined English teachers' perceptions of using YouTube videos in vocabulary instruction and the challenges they encounter when integrating this medium into classroom practice. A quantitative survey with a descriptive design was employed, involving 55 English teachers from junior high schools in Penajam Paser Utara Regency. Data were collected through a questionnaire adapted from Al Amin and Aziz (2023) and Scott and Walczak (2009), covering six indicators: absorption, understanding, evaluation, perceived ease of use, perceived usefulness, and external challenges. Data were analyzed descriptively using percentages and mean scores. Results showed that teachers held generally positive perceptions of YouTube as a vocabulary learning tool, with absorption, understanding, and evaluation indicators falling into the good category, suggesting that audiovisual context supports vocabulary comprehension and sustains learner motivation. Teachers nonetheless reported persistent challenges, namely unreliable internet connectivity, the time burden of curating suitable videos, the risk of students being distracted by unrelated content, and limited institutional support for technology integration. These findings indicate that while YouTube holds strong potential as a vocabulary learning medium, its effective use depends on teachers' digital competence, deliberate pedagogical planning, and adequate institutional backing.